Information Disclosure and the Transition to a Low-Carbon Economy: Climate-Related Risk in the UK and France. (10th December 2019) - Webster, Emily
Abstract: Over the last several years there has been increasing recognition and acceptance of the threat that climate change poses to global financial stability and the concurrent need for corporations to identify and account for both climate risks and their impacts on the environment. This has resulted in the emergence of climate risk disclosure (CRD) as a voluntary standard as well as movement on the domestic level to introduce mandatory CRD, demonstrated by the introduction of CRD framework legislation in France. This article conducts a comparative analysis of France and the UK—countries that are adopting divergent methods of legal development towards CRD—to analyse the potential of CRD as a policy tool to aid towards climate change mitigation and the transition to a low-carbon economy, and evaluate how effectively this is being achieved in practice.